Pengaruh Literasi Keuangan, Gaya Hidup, dan Penggunaan Financial Technology terhadap Pengelolaan Keuangan pada Mahasiswa Program Studi S1 Manajemen Universitas 17 Agustus 1945 Surabaya - Dewi Rahayu; Ulfi Pristiana (Pusat Riset dan Inovasi Nasional, 2025)
In contemporary society, characterized by swift technological advancement and modernization, students face mounting challenges in financial management due to consumption-driven behaviors and insufficient financial literacy. This investigation examines the correlations between financial literacy, lifestyle choices, and financial technology adoption in shaping financial management practices among students enrolled at the University of 17 August 1945 Surabaya. The methodology employs quantitative research techniques, utilizing questionnaire-based surveys administered to 100 participants selected from the management academic division. Statistical examination of the collected data reveals that both financial literacy and lifestyle exhibit substantial effects on students' monetary decision-making processes. Additionally, while financial technology demonstrates considerable influence on financial management outcomes, its beneficial implementation depends significantly on individual proficiency and practical familiarity with these tools.